EFFECTS OF TGF-Β3/PDGF-BB-HEPARIN-HYALURONIC ACID HYDROGEL ON RABBIT KNEE OSTEOARTHRITIS - Zhiyu Wang; Lei Shi; Weitong Chen; Bo Feng (Journal of Animal and Plant Sciences, 2026)
Current treatments for knee osteoarthritis (KOA) can alleviate symptoms but fail to repair damaged articular cartilage, while long-term use may lead to side effects. This study aimed to investigate the role of transforming growth factor (TGF)-β3-platelet-derived growth factor (PDGF)-B chain homodimer (BB)/heparin-hyaluronic acid (HA) hydrogel in rabbit KOA to achieve effective articular cartilage repair. Methacrylated hyaluronic acid (HAMA) and heparin (HepMA) were synthesized and utilized as matrices to prepare HepMA-HAMA hydrogel microspheres (MSs). Subsequently, the MSs were co-incubated with TGF-β3 and PDGF-BB to fabricate heparin-HA hydrogel MSs loaded with dual growth factors (HepMA-HAMA@DGFs). The drug loading, release , degradation and biocompatibility characteristics of the prepared hydrogel MSs were examined. New Zealand rabbits were utilized as experimental animals, and a KOA rabbit model was established. Physiological saline (Model group), HA (HA group), hydrogel MSs (HepMA-HAMA group and HepMA-HAMA@DGFs group) were injected into the joint cavity. Healthy rabbits served as the control. Behavioral analysis, knee joint histology, and expression differences of matrix metalloproteinase-13 (MMP-13), tissue inhibitor of metalloproteinases-1 (TIMP-1), and vascular endothelial growth factor (VEGF) in knee articular cartilage were calculated. The MSs exhibited sustained cumulative drug release and in vitro degradation. Co-culturing HepMA-HAMA@DGFs MSs with mouse bone marrow mesenchymal stem cells (MSCs) showed minimal changes in cell growth. In rabbits, the model group exhibited increased Lequesne MG scores, upregulated expression of MMP-13 and VEGF in knee articular cartilage, and downregulated expression of TIMP-1 versus Control (P<0.05). HepMA-HAMA and HepMA-HAMA@DGFs groups showed reduced Lequesne MG scores, downregulated expression of MMP-13 and VEGF in knee articular cartilage, and upregulated expression of TIMP-1 versus Model group (P<0.05). Compared with the HepMA-HAMA group, HepMA-HAMA@DGFs group exhibited decreased Lequesne MG scores, downregulated expressions of MMP-13 and VEGF in knee articular cartilage of rabbits, and upregulated expression of TIMP-1 (P<0.05). These findings indicate that HepMA-HAMA@DGFs hydrogel MSs have favorable drug release properties, degradation performance, and biocompatibility. Furthermore, HepMA-HAMA@DGFs hydrogel MSs can reduce the expression of MMP-13 and VEGF in KOA cartilage of rabbits, increase the expression of TIMP-1, and promote cartilage repair, thereby exerting therapeutic effects in the treatment of KOA in rabbits.
Keywords: TGF-β3-PDGF-BB/heparin-hyaluronic acid hydrogel; knee osteoarthritis; drug release rate; growth factor; cartilage repair